Morphometric indicators of orbit in adults - S. O. Dubyna; M. I. Yabluchanskyi (Zaporožskij Medicinskij Žurnal)
Aim. Morphometry of orbit is one of the prerequisites planning and performance of surgical interventions after injuries of craniofacial zone.